Long-term follow-up results of patients with left bundle branch pacing and exploration for potential factors affecting cardiac function - Hu, Qingyun; Lu, Wenzhao; Chen, Keping; Dai, Yan; Lin, Jinxuan; Xu, Nan; Lin, Jingru; Chen, Ruohan; Li, Yao; Cheng, Chendi; Zhou, Yu’an; Zhang, Shu (Frontiers in Physiology, 2022)
Background: Left bundle branch pacing (LBBP) is an alternative strategy for His bundle pacing (HBP). This study aimed to analyze the long-term performance of LBBP and the potential factors affecting long-term cardiac function. Methods: Patients with LBBP were continuously enrolled from January 2018 to August 2020. Pacing parameters, electrocardiogram (ECG), and echocardiography were collected. The anatomic position of LBBP leads was described by echocardiographic and fluoroscopic parameters. Results: A total of 91 patients with a median follow-up of 18 months were enrolled. Most patients maintained stable pacing parameters during follow-up. The intra-septal position of the 3830 lead also remained stable as the distance from the lead tip to the left surface of the ventricular septum was 0.4 (0, 1.4) mm. The overall level of left ventricular ejection fraction (LVEF) slightly increased. 59 patients had improved LVEF (∆LVEF > 0), while 28 patients had unchanged or reduced LVEF (∆LVEF ≤ 0). The declines of baseline LVEF, ∆ Paced QRSd, and corrected longitudinal distance (longit-dist) of lead-implanted site correlated with LVEF improvement, and these three factors had negative linear correlations with ∆LVEF. Patients with tricuspid valve regurgitation (TVR) deterioration had longer follow-up duration (20.5 vs. 15.0 months, p = 0.01) and shorter Lead-TVA-dist (18.6 vs. 21.6 mm, p = 0.04) than those without TVR deterioration. Conclusion: Patients with LBBP generally remained stable in pacing performance, anatomic lead positions, and cardiac function in long-term follow-up. Baseline LVEF, ∆ Paced QRSd, and corrected longit-dist might be associated with potential LVEF decrease, which required further confirmation.